A study of the mini bus service in Butterworth / Ami Adeela A.Rahman - A.Rahman, Ami Adeela (Faculty of Civil Engineering, 2007)
Nowadays, transportation is an important aspect in the economic development of society. A nation of any country cannot achieve the maximum productivity of its people without transportation. The transportation system in a developed country consists of vehicles, terminal facilities and control systems. Malaysia is a develop country but its public transportation system is not parallel with its development. This report discussed a study on mini bus service in Butterworth where the stage of public bus is not frequent. A major advantage of mini bus as a public transportation is it could operate on a variety of service plan. The service plan offered would depend based on level of demand and trip purpose. Mini bus also can respond to changes in demand and types of services needed throughout the day. The final report of a case study on mini bus service in Butterworth includes statistical analysis based on bus commuter’s feedback by filled up the questionnaires and quantitative survey of total number of passengers. The overall finding is the supply of public bus is insufficient to accommodate public transport demand and should be improved in the future. Without perfect planning regarding the issue facing by bus commuters, our country will not achieve our mission as a proper developed country.